Targeted modulation of cell differentiation in distinct regions of the gastrointestinal tract via oral administration of differently PEG-PEI functionalized mesoporous silica nanoparticles - Diti Desai; Neeraj Prabhakar; Veronika Mamaeva; Didem Şen Karaman; Iris AK Lähdeniemi; Cecilia Sahlgren; Jessica M Rosenholm; Diana M Toivola (Dove Medical Press Ltd.(Dovepress), 2025)
Targeted delivery of drugs is required to efficiently treat intestinal diseases such as colon cancer and inflammation. Nanoparticles could overcome challenges in oral administration caused by drug degradation at low pH and poor permeability through mucus layers, and offer targeted delivery to diseased cells in order to avoid adverse effects. Here, we demonstrate that functionalization of mesoporous silica nanoparticles (MSNs) by polymeric surface grafts facilitates transport through the mucosal barrier and enhances cellular internalization. MSNs functionalized with poly(ethylene glycol) (PEG), poly(ethylene imine) (PEI), and the targeting ligand folic acid in different combinations are internalized by epithelial cells in vitro and in vivo after oral gavage. Functionalized MSNs loaded with γ-secretase inhibitors of the Notch pathway, a key regulator of intestinal progenitor cells, colon cancer, and inflammation, demonstrated enhanced intestinal goblet cell differentiation as compared to free drug. Drug-loaded MSNs thus remained intact in vivo, further confirmed by exposure to simulated gastric and intestinal fluids in vitro. Drug targeting and efficacy in different parts of the intestine could be tuned by MSN surface modifications, with PEI coating exhibiting higher affinity for the small intestine and PEI-PEG coating for the colon. The data highlight the potential of nanomedicines for targeted delivery to distinct regions of the tissue for strict therapeutic control.